PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA AIR TERJUN GURUH GEMURAI DESA KASANG KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Anggraini, Axelia Dessy; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research purposed to find out how the community participation in the management of and what factors become the impetus the community to participate in the sights of Guruh Gemurai Waterfalls.This research uses qualitative methode with descriptive approach. The subject of research consist of purposive sampling which produces 3 key informants. While data collection techniques in this study using obsevation, interviews and documentations.Based on the research that has been done, the community participation in managing Kasang village attractions Guruh Gemurai waterfalls is still insufficient, due to the communities who have not yet realized for keeping and caring for tourist attractions. And there are two factors impetus community participation that is the economic factor and the natural environment. Factor economic that is becoming a major factor impetus the community participate on Kasang villageKeywords: Community participation, Kasang Village, Guruh Gemurai Waterfalls, Kuantan Singingi Regency